Integrated Management of Type-2 Diabetes Mellitus Associated Hyperlipidemia with Naturopathy, Yoga and Diet Control: A Case Report - Singh, Poonam (International Research Journal of Ayurveda & Yoga, 2022)
Diabetes mellitus is a syndrome-like systemic problem that has multi-organ complications. Early intervention may prevent several manifestations of different organs. Diabetes disrupts the healing process, immunity, and may result in renal complications, and retinopathies. Our increasing sedentary lifestyle, bad food habits and lifestyle choices like smoking and drinking are responsible for the progression of this dreaded disease. Various causes of diabetes may be pathological, hereditary, congenital, faulty lifestyle, pancreatic malfunction and the build-up of toxins in the body. Many treatment modalities are available for the management of this condition but none of these give promising results with long term drug dependency. The drug used in the treatment may have unwanted side effects. Yoga acts like a panacea for diabetes. Yoga provides an ideal cure for diabetes management. Yoga therapy is perceivably quick in the earlier stages and extremely beneficial after continuous practice for hyperglycemia. Yoga improves the psychological makeup and general feeling of well-being. In the present case report, I have discussed a case of diabetes associated with hyperlipidemia with naturopathy, yoga, and diet modification.